Mechanochemical routes for the synthesis of acetyl- and bis-(imino)pyridine ligands and organometallics. Issue 47 (23rd October 2018) - Shaw, Thomas E.; Shultz, Lorianne R.; Garayeva, Louiza R.; Blair, Richard G.; Noll, Bruce C.; Jurca, Titel
Abstract : Mechanochemical synthesis, conducted by ball milling, affords rapid access to acetyl- and bis(imino)pyridine ligands and acetyl(imino)pyridine cobalt species. Abstract : Organometallic precatalysts play a pivotal role in organic synthesis. However, their preparation often relies on multiple time, energy, and solvent intensive steps, including the synthesis of supporting organic ligand structures, and finally installation on the desired metal centres. We report the sustainable mechanochemical synthesis of acetyl- and bis-(imino)pyridine pincer complexes, a ubiquitous ligand class for organometallic precatalysts. The approach is extended to the one-pot synthesis of acetyl(imino)pyridine-CoCl2, where the ligand is formed in situ .